On the Impact of the Number of Tiles and Partitioning of RISs on the Maximum Achievable Intensity (Jurnal Elektronika dan Telekomunikasi, 2024)
Reconfigurable intelligent surface (RIS) is a key technology to enable the concept of smart radio environment (SRE) which is envisioned to meet the ever-increasing demands of connectivity in the upcoming decade. However, most existing works consider a RIS that is seen as a whole surface. In this paper, we study the performance of a RIS that consists of multiple tiles, each of which is capable of performing certain wave manipulation, by deriving the physics-compliant analytical formulation of the received signal at the receiver. We also introduce the numerical approximation of the signal for different operating regimes and different functionalities. Based on the obtained result, we study the impact of the number of fixed-sized tiles and partitioning of a fixed-sized RIS on the maximum achievable intensity. The validity of our findings is confirmed through extensive simulation results.